1929 Pa. Laws 777–78, No. 329, § 3 - (:unkn) unknown (General Publisher, 1929)
Prohibited being armed with a machine gun while committing a crime. Punishable by imprisonment with solitary confinement up to 10 years.
--
Keywords: MACHINE GUN RESTRICTION